Deputy Sheriff illustration - Thomas Hart Benton (artist):::Creator::: (2024)
The Deputy Sheriff from The Grapes of Wrath, c. 1940, v.2, p.289, illustrated edition, by Thomas Hart Benton, a native of eastern Oklahoma, who was assigned to draw archetypal Oklahomans for 20th Century Fox as the studio believed that would make the casting more accurate. "And then the raids, the swoop of armed deputies on the squatters' camps. Get out. Department of Health orders. This camp is a menace to health. Where we gonna go?"